Compliment Responses by Indonesian Lecturers of English - Manipuspika, Yana Shanti; Sudarwati, Emy (SOSIOHUMANIKA, 2016)
ABSTRACT: This paper analyzed the CRs (Compliment Responses) performed by Indonesian lecturers of English at the English Department UNIBRAW (University of Brawijaya) in Malang City, East Java, Indonesia, when interacting with their colleagues in the workplace based on sex differences. This research used qualitative approach to analyze the compliment responses performed by the lecturers. The compliment responses were analyzed based on Robert K. Herbert (1986)âs theory. It was shown that the responses given are various. The lecturers are most likely to accept compliments by appreciation token, both in verbal and non-verbal responses. Moreover, most of the responses are combination of two or more types of CRs. In relation to gender, male and female participants give similar responses, yet male tend to use question preceding or following the responses, while female tend to use comment avoidance. Regarding the L2 (Second Language) competence, this study found out that the lecturers still retain their L1 (First Language) culture in appreciating a compliment, regardless their competence in English, both linguistically and culturally. In conclusion, the variety of compliment responses given by lecturers of English at the English Department UNIBRAW might be caused by their habit of expressing themselves freely without too strictly bound to the norm in which they are related. Complimenting events for them can be used as media to create feeling of solidarity.KEY WORD: Compliment Responses; Indonesian Lecturers; English; Gender; Culture.Â RESUME: âRespon Pujian yang Diberikan oleh Dosen Indonesia Pengajar Bahasa Inggrisâ. Studi ini menganalisis respon pujian yang dilakukan oleh dosen Indonesia pengajar Bahasa Inggris di Program Studi Sastra Inggris UNIBRAW (Universitas Brawijaya) di Kota Malang, Jawa Timur, Indonesia, saat berinteraksi dengan rekan-rekan mereka di tempat kerja. Pemilihan responden didasarkan atas perbedaan jenis kelamin. Penelitian ini menggunakan pendekatan kualitatif untuk menganalisis tanggapan pujian yang diberikan oleh para dosen. Respon pujian dianalisis berdasarkan teori Robert K. Herbert (1986). Hasil penelitian menunjukan bahwa respon yang diberikan itu beragam. Para dosen cenderung menerima pujian dengan menggunakan tipe âappreciation tokenâ (bentuk apresiasi), baik dalam respon verbal maupun non-verbal. Selain itu, sebagian besar respon pujian merupakanÂ  kombinasi dari dua tipe respon pujian atau lebih. Berkaitan dengan jenis kelamin, responden laki-laki dan perempuan memberikan respon yang serupa, namun laki-laki cenderung menggunakan pertanyaan sebelum dan setelah respon pujian, sementara perempuan cenderung menggunakan âcomment avoidanceâ (menghindari komentar). Dalam kaitannya dengan kompetensi L2 (Bahasa Kedua atau Bahasa Asing), penelitian ini menemukan bahwa para dosen masih mempertahankan budaya L1 (Bahasa Pertama atau Bahasa Ibu) mereka dalam menghargai pujian, terlepas dari kompetensi mereka dalam bahasa Inggris, baik dalam bahasa maupun budayanya. Dari penelitian ini dapat disimpulkan bahwa berbagai respon pujian yang diberikan oleh dosen bahasa Inggris di Program Studi Sastra Inggris UNIBRAW mungkin disebabkan oleh kebiasaan mereka untuk mengekspresikan diri secara bebas tanpa terlalu terikat pada kriteria tertentu. Memberikan pujian bagi mereka dapat digunakan sebagai media untuk menciptakan rasa solidaritas. Â KATA KUNCI: Respon Pujian; Dosen Indonesia; Bahasa Inggris; Jenis Kelamin; Budaya.Â Â About the Authors: Yana Shanti Manipuspika, M.Appl.Ling. and Emy Sudarwati, M.Pd. are the Lecturers at the Study Program of English Literature, Department of Language and Literature FIB UNIBRAW (Faculty of Humanities, Brawijaya University), Jalan Veteran, Malang City 65145, East Java, Indonesia. For academic interests, the authors can be contacted via e-mail at: yana.manipuspika@gmail.comHow to cite this article? Manipuspika, Yana Shanti & Emy Sudarwati. (2016). âCompliment Responses by Indonesian Lecturers of Englishâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(1) May, pp.105-116. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (September 26, 2015); Revised (March 2, 2016); and Published (May 20, 2016).